Schottky defects in cubic lattice of SrTiO3 - Stashans, A. (2008)
Structural and electronic properties produced by formation of Schottky defects in cubic structure of SrTiO3 crystal are investigated by means of a quantum-chemical simulation based on the Hartree-Fock methodology. The occurrence of Sr partial Schottky defect (VSr+VO) and two types of Ti partial Schottky defects (VTi+2VO) is modeled using a supercell containing 135 atoms. Vacancy-induced changes in the positions of their neighboring atoms are analyzed in light of the computed electron density redistribution in the defective region of supercell. The observed local one-electron energy levels in the gap between the upper valence band and the conduction band can be attributed to the presence of anion and cation vacancies. © 2008 Elsevier Ltd. All rights reserved.